Preparation of aurum chloride complex and its use for industrial acetylene hydration catalyst process - Kokhan, Ivan; Kudryavtsev, Sergey; Merzhyievskyi, Danylo (Eastern-European Journal of Enterprise Technologies, 2022)
The use of a modern homogeneous metal complex catalyst for the hydration of acetylenes is being investigated. The process is relevant both for the industry of basic organic synthesis and for the perfume industry. The analysis of existing processes used in industry for the production of acetaldehyde was carried out. Significant shortcomings of existing processes are revealed: low environmental friendliness and high energy consumption. To solve this problem, the reaction of hydration of an acetylene compound was studied using a modern homogeneous catalyst based on gold, which is not toxic. The study was conducted by selecting aliquots during the reaction. Using the 1H NMR spectroscopy method, the conversion values of phenylacetylene were calculated for the time values corresponding to the moments of aliquot sampling. The reaction order with respect to phenylacetylene was calculated and the reaction constant under the reaction conditions was calculated. When reacting in the presence of the proposed catalyst, a conversion of phenylacetylene of 86.96 % is achieved in 3 hours. The data obtained provide grounds for carrying out the process of catalytic hydration of acetylenes, namely phenylacetylene, with the production of acetophenone, which is important for use in the perfume industry. The data obtained can be applied to the process of hydration of acetylene with the formation of acetaldehyde, which is widely used in the industry of basic organic synthesis. For the process of catalytic hydration of acetylene compounds, a hardware design is proposed, a gas-liquid reactor with a changing hydrodynamic situation, which, together with the product separation column, is combined into a single installation. Using an optimized method, a catalyst based on gold chloride was synthesized from a gold alloy.